Effects of Early Surgical Exploration in Suspected Barotraumatic Perilymph Fistulas - Park, Ga Young (Korean Society of Otorhinolaryngology-Head and Neck Surgery, 2012)
OBJECTIVES: Treatment of traumatic perilymph fistula (PLF) remains controversial between surgical repair and conservative therapy. The aim of this study is to analyze the outcomes of early surgical exploration in suspected barotraumatic PLF. METHODS: Nine patients (10 cases) who developed sudden sensorineural hearing loss and dizziness following barotrauma and underwent surgical exploration with the clinical impression of PLF were enrolled. Types of antecedent trauma, operative findings, control of dizziness after surgery, postoperative hearing outcomes, and relations to the time interval between traumatic event and surgery were assessed retrospectively. RESULTS: All patients had sudden or progressive hearing loss and dizziness following trauma. Types of barotrauma were classified by the origin of the trauma: 4 external (car accident, slap injury) and 6 internal traumas (lifting, nasal blowing, straining). Surgical exploration was performed whenever PLF was suspected with the time interval of 2 to 47 days after the trauma. The possible evidence of PLF was found during surgery in 9 cases: a fibrous web around the oval window (n=3), fluid collection in the round window (RW; n=6) and bulging of the RW pseudomembrane (n=1). In every patient, vestibular symptoms disappeared immediately after surgery. The hearing was improved with a mean gain of 27.0±14.9 dB. When the surgical exploration was performed as early as less than 10 days after the trauma, serviceable hearing (≤40 dB) was obtained in 4 out of 7 cases (57.1%). CONCLUSION: Sudden or progressive sensorineural hearing loss accompanied by dizziness following barotrauma should prompt consideration of PLF. Early surgical exploration is recommended to improve hearing and vestibular symptoms.